Nurses’ Knowledge of Blood Culture Sampling Procedure - Wulan Ardhana Iswari; Chrysanti Murad; Ida Parwati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: False-positive blood culture results due to contaminated samples have shown to increasepatients’ health costs, including the use of broad spectrum antibiotics and prolonged hospital length ofstay. While previous research have suggested that increasing staff knowledge on proper specimen collectionlowers contamination rates significantly, staff’s current knowledge of hospital-recommended samplecollection procedure have yet to be assessed in Dr. Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.Methods: This was a cross-sectional descriptive study on 81 Emergency Department nurses in Dr. HasanSadikin General Hospital, Indonesia. Subjects were asked to complete a questionnaire in order to measuretheir knowledge of blood culture sampling procedure in accordance with the hospital’s standard operatingprocedure.Results: Among 81 subjects enrolled, 51 managed to adequately describe the prerequisites in proper bloodculture sampling procedure and their purpose as dictated by Dr. Hasan Sadikin General Hospital’s standardoperating procedure.Conclusions: Up to 67% of nurses conducting blood sampling procedure in Dr. Hasan Sadikin GeneralHospital’s Emergency Department understood the prerequisites of hospital-recommended blood culturesampling procedure and their purpose.